A thermochromic europium(iii) room temperature ionic liquid with thermally activated anion–cation interactions. Issue 5 (5th December 2016) - Monteiro, Bernardo; Outis, Mani; Cruz, Hugo; Leal, João Paulo; Laia, César A. T.; Pereira, Cláudia C. L.
Abstract : An observable and reversible case of thermochromism due to an unusual interaction between the countercation and the ligand of an europium(iii ) tetrakis-β-diketonate room temperature ionic liquid is reported. Abstract : We report the first example of an observable and reversible case of thermochromism due to the interaction of an alkylphosphonium (P6, 6, 6, 14 ) + with a β-diketonate (1, 1, 1, 2, 2, 3, 3-heptafluoro-7, 7-dimethyloctane-4, 6-dionate-fod) of an europium(iii ) tetrakis-β-diketonate room temperature ionic liquid. This thermochromism is characterized by the conversion of a light yellow viscous liquid, at room temperature, to a reddish substance close to 80 °C. The reversibility of this optical effect was highlighted by the thermal stability of the Eu(iii ) complex.